STUDENTS’ PERCEPTION OF BIOLOGY LEARNING AT KEPANJEN ISLAMIC SENIOR HIGH SCHOOL - Iqbal, Mochammad (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2022)
Biology is one of the subjects in the science specialization. Opinions from students stating that biology is the easiest subject among science specialization subjects. However, some students have difficulties studying biology for a variety of reasons, including the teacher's teaching style, the student's learning style, the students' unfavorable opinion of the course, and a lack of learning materials. This study aims to find out the student's perception of biology learning at Kepanjen Islamic senior high school. This study uses a descriptive quantitative approach. The sample in this study was class X students with the sampling technique carried out by proportioned stratified random sampling. Data collection techniques used in this study were questionnaires and interviews. The score from the questionnaire data is calculated by percentage statistics. The finding reveals that the perception of class X students on the implementation of the biology learning process as a whole is in enough category with a percentage of 79.17%. Of the five activities in the learning process, there are two categories, namely gathering information and communicating with ‘good,’ category, and those having ‘enough’ categories, namely observing, asking questions, and associating or processing information.